Дослідження властивостей та мікроструктури швидкорізальних сталей після плазмового поверхневого азотування - Мазур, В. О. (НТУ "ХПІ", 2015)
Вивчено вплив технологічних параметрів плазмово-хімічної обробки на структуру та властивості швидкорізальних сталей після плазмового азотування. Досліджено розподіл азоту та фаз, що його містять, у зміцненій зоні в залежності від складу плазмоутворюючого газу та методу поверхневого зміцнення (без оплавлення та з оплавленням поверхневого шару). Досліджено структуру та фазовий склад сталі після плазмо-хімічного зміцнення. Отримані результати забезпечують великий ресурс для підвищення експлуатаційних властивостей швидкорізальних сталей, а через це й працездатності інструменту з цих сталей.

The research of technological parameters of plasma-chemical treatment on the structure and properties of high-speed steel after plasma nitriding has been conducted. The distribution of nitrogen and phases that contain it, in a consolidated area depending on the composition and method of gas plasma surface hardening (without melting of the surface layer) has been conducted. The distribution of microhardness depth treatment drastically changed in the transition from treatment without melting to the plasma mikromelting. With partial mixing of the molten layer convective flows from the action of the plasma jet microhardness distribution aligned. Found that the plasma chemical processing formed multilayer composition consisting of nitrided layer and plasma surface modification area, a total depth of 4.5 - 5 mm. This provides a great resource to enhance the performance properties of high-speed steels, and because of this instrument and efficiency of these steels.
Study of properties and microstructure speed steel after surface plasma nitriding
Keywords: плазмово-хімічна обробка; поверхневе зміцнення; фазовий склад; мікротвердість; plasma; nitriding; strengthening; phase composition; microhardness; nitride